2016
DOI: 10.1007/978-3-319-46100-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Anyboard: A Platform for Hybrid Board Games

Abstract: Making hybrid board games that mix the interactivity of video games with the social impact of board games is challenging. While the design process needs to take into account elements from the digital and analog domains, building prototypes requires dealing with diverse technologies in the field of Tangible Interfaces and Interactive Tabletop and Surfaces. Anyboard provides theoretical tools to map traditional board game interaction to the hybrid medium and lightweight technology tools to facilitate game protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…On completion of the authors' experimental study, they found that, 'Analysis of covariance revealed that both boys and girls of the game intervention group showed a higher test performance, compared to students of the control group. ' Mora et al [14] proposes a framework for developing interactive board games based on barcodes and RFID technology. To develop a game for learning starting from a game concept, one has to define the logic and rules, the interactions of the players with the game tokens, and the interaction among them as well as customization of the software libraries, production of objects that are not computerized, like the board and cases to tailor the appearance of tokens, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On completion of the authors' experimental study, they found that, 'Analysis of covariance revealed that both boys and girls of the game intervention group showed a higher test performance, compared to students of the control group. ' Mora et al [14] proposes a framework for developing interactive board games based on barcodes and RFID technology. To develop a game for learning starting from a game concept, one has to define the logic and rules, the interactions of the players with the game tokens, and the interaction among them as well as customization of the software libraries, production of objects that are not computerized, like the board and cases to tailor the appearance of tokens, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%